(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Distributed computing has helped enthusiasm for a worldview called Datamining-as-a-service. This framework is useful for the organizations lack in specialized persons and processing asset empower to compute ,it enforces them to outsource their information to the outsider for data mining undertakings. In this work, we examine the strategy to safeguard security for frequent itemset mining in outsourced exchange databases and utilizing FiDoop calculation to process the infrequent itemsets from the outsourced datasets on the server side. A novel strategy used to accomplish k-support anonymity in light of measurable perceptions on the datasets to safeguard the security of the outsourced dataset. To decide frequent itemset at the distributed computing side from the database that gotten from various associations by utilizing a parallel mining for frequent itemsets, algorithm called FiDoop utilizing the programming model of MapReduce. FiDoop coordinate frequent itemset ultrametric (FIU)tree rather than customary FP-tree to empower the packed stockpiling of the mined information and to stay away from conditional pattern based information. Three MapReduce tasks are utilized to mine the information from the outsourced data. In the significant third MapReduce undertaking, the mappers autonomously break down itemsets that delivered from second MapReduce, the reducers perform blend operations by building FIU-tree.